(untitled) (Research, Society and Development, 2018)
Population aging becomes a reality not only in developed countries, but in developing nations, as in the case of Brazil. In this context, it is necessary to rethink the role of the State, society and the family in order to improve the support necessary for the development of protection and assistance for the elderly. In this sense, the objective of this study is to share a reflection about aging from the perceptions of a researcher recorded in his field diary. The present reflection originated through the realization of the PhD thesis of the Stricto Sensu Postgraduate Program in Environment and Development, entitled "The longevity of the population of Vale do Taquari-RS: new trends and needs." A discussion of the results of the research was discussed, as well as aspects about current legislation, the aging of the 21st century and some important considerations. It is considered that the current scenario is a modification in the social processes of aging and it is about the need for effective political interventions in the care of this growing segment of individuals that requires specialized care according to its characteristics, in which its autonomy should prevail in the decision.